Determinación de metabolitos y extracción de pectina del albedo de Citrus medica L. (cidra) - López Z., Stela (2000)
The chemical bromatological determination of albedo, Citrus medica L. (Citron) demostrated high caloric and ascorbic acid values and low fat contents. The pectin, as calcium pectate was high. When carrying out the pectin's characterization, high percentage of methoxyle (8,55%) was found and therefore a high degree of esterification (69,49). In aquous, methanolic and ethanolic extracts of albedo citron the presence of flavonoid, coumarin , amino acid and phenolic compounds was deter mine.